Students’ attitudes toward the internet usage for learning - Dodi Erwin Prasetyo (EnJourMe (English Journal of Merdeka) : Culture, Language, and Teaching of English, 2021)
This paper examined students’ attitudes toward the use of internet for their learning and measured the differences between male and female students on the usage of internet-assisted in their learning. The participants of this study were 27 senior high school students in East Java, Indonesia, consisted of 6 male and 21 female. The data was gathered through questionnaire. The findings proved that majorities of students felt positive attitudes toward the use of internet for their learning. There were no differences between male and female students on their attitude of internet usage. Suggestions are for pedagogical as well as future researches.   DOI: 10.26905/enjourme.v6i2.6583